Efficient hydrogenation of organic carbonates, carbamates, and formates indicates alternative routes to methanol based on CO2 and CO - Balaraman, Ekambaram; Gunanathan, Chidambaram; Zhang, Jing; Shimon, Linda J. W.; Milstein, David (Nature Chemistry, 2011)
Catalytic hydrogenation of organic carbonates, carbamates and formates is of significant interest both conceptually and practically, because these compounds can be produced from CO2 and CO, and their mild hydrogenation can provide alternative, mild approaches to the indirect hydrogenation of CO2 and CO to methanol, an important fuel and synthetic building block. Here, we report for the first time catalytic hydrogenation of organic carbonates to alcohols, and carbamates to alcohols and amines. Unprecedented homogeneously catalysed hydrogenation of organic formates to methanol has also been accomplished. The reactions are efficiently catalysed by dearomatized PNN Ru(II) pincer complexes derived from pyridine- and bipyridine-based tridentate ligands. These atom-economical reactions proceed under neutral, homogeneous conditions, at mild temperatures and under mild hydrogen pressures, and can operate in the absence of solvent with no generation of waste, representing the ultimate ‘green’ reactions. A possible mechanism involves metal–ligand cooperation by aromatization–dearomatization of the heteroaromatic pincer core.